2013
DOI: 10.1590/s0034-70942013000100002
|View full text |Cite
|
Sign up to set email alerts
|

Hipertermia maligna no Brasil: análise da atividade do hotline em 2009

Abstract: Background and objectives: Malignant hyperthermia (MH) is a pharmacogenetic disease that causes abnormal hypermetabolic reaction to halogenated anesthetics and/or depolarizing muscle relaxants. In Brazil, there is a hotline telephone service for MH since 1991, available 24 hours a day in São Paulo. This article analyzes the activity of the Brazilian hotline service for MH in 2009. Methods: Prospective analysis of all phone calls made to the Brazilian hotline service for MH from January to December 2009. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 12 publications
0
1
0
13
Order By: Relevance
“…All of them have received training that consisted of an intensive MH course, with theoretical and practical information for the diagnosis, treatment and follow-up of patients with MH through Unifesp's CEDHIMA. 12,13 It can be concluded that MH is a rare and serious disease for susceptible individuals undergoing anesthesia using volatile agents. Early recognition of signs and symptoms for proper treatment is of paramount importance, as delayed diagnosis and treatment increases morbidity and mortality from the disease.…”
Section: Discussionmentioning
confidence: 99%
“…All of them have received training that consisted of an intensive MH course, with theoretical and practical information for the diagnosis, treatment and follow-up of patients with MH through Unifesp's CEDHIMA. 12,13 It can be concluded that MH is a rare and serious disease for susceptible individuals undergoing anesthesia using volatile agents. Early recognition of signs and symptoms for proper treatment is of paramount importance, as delayed diagnosis and treatment increases morbidity and mortality from the disease.…”
Section: Discussionmentioning
confidence: 99%
“…Em 1991 foi criado um serviço de atendimento telefônico para HM no Brasil, disponível durante 24 horas do dia, chamado Hotline (+55-11-55759873). O serviço brasileiro fica em São Paulo, no Hospital São Paulo, Escola Paulista de Medicina da Universidade Federal de São Paulo (UNIFESP) 1 . Desde 2009, as chamadas são redirecionadas para um grupo formado por dois supervisores, que são também pesquisadores especializados em HM, e oito médicos 1 .…”
Section: Discussionunclassified
“…A hipertermia maligna (HM) é uma doença farmacogenética, de herança autossômica dominante, caracterizada por reação hipermetabólica anormal a agentes anestésicos inalatórios do grupo dos halogenados, tais como halotano, isoflurano, sevoflurano e desflurano e aos relaxantes musculares despolarizantes, como a succinilcolina 1,2 .…”
Section: Introductionunclassified
“…No Brasil, existe desde 1991 o serviço Hotline, para acompanhar por telefone (+55-11-5575-9873) a progressão dos episódios de HM e prestar assistência. Publicou-se uma investigação de sua atividade no ano de 2009, quando foram estimadas 77 crises anuais 4 . Em uma análise das fichas de notificação dos pacientes com suspeita pessoal ou familiar de HM entre 1997 e 2010, a suscetibilidade foi confirmada em 79,4% dos 92 parentes investigados com teste de contratura muscular in vitro 5 .…”
Section: Introductionunclassified